The focal adhesion kinase Pyk2 links Ca2+ signalling to Src family kinase activation and protein tyrosine phosphorylation in thrombin-stimulated platelets - Canobbio, I.; Cipolla, L.; Guidetti, G.; Manganaro, D.; Visconte, C.; Kim, S.; Okigaki, M.; Falasca, Marco; Kunapuli, S.; Torti, M. (Portland Press Ltd, 2015)
In blood platelets, stimulation of G protein-coupled receptors (GPCRs) by thrombin triggers the activation of Src family kinases (SFKs), resulting in the tyrosine-phosphorylation of multiple substrates, but the mechanism underlying this process is still poorly understood. In the present study, we show that the time-dependent protein-tyrosine phosphorylation triggered by thrombin in human or murine platelets was totally suppressed only upon concomitant chelation of intracellular Ca(2+) and inhibition of SFKs. Thrombin-induced activation of SFKs was regulated by intracellular Ca(2+) and accordingly the Ca(2+) ionophore A23187 was sufficient to stimulate SFKs. A23187 also triggered the phosphorylation and activation of the Ca(2+)-dependent focal adhesion kinase Pyk2 and Pyk2 activation by thrombin was Ca(2+)-dependent. Stimulation of SFKs by thrombin or A23187 was strongly reduced in platelets from Pyk2 knockout (KO) mice, as was the overall pattern of protein-tyrosine phosphorylation. By immunoprecipitation experiments, we demonstrate that Lyn and Fyn, but not Src, were activated by Pyk2. Inhibition of SFKs by PP2 also reduced the phosphorylation of Pyk2 in thrombin or A23187-stimulated platelets. Analysis of KO mice demonstrated that Fyn, but not Lyn, was required for complete Pyk2 phosphorylation by thrombin. Finally, PP2 reduced aggregation of murine platelets to a level comparable to that of Pyk2-deficient platelets, but did not have further effects in the absence of Pyk2. These results indicate that in thrombin-stimulated platelets, stimulation of Pyk2 by intracellular Ca(2+) initiates SFK activation, establishing a positive loop that reinforces the Pyk2/SFK axis and allows the subsequent massive tyrosine phosphorylation of multiple substrates required for platelet aggregation.